2006
DOI: 10.1007/s10548-006-0010-1
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Characterization and Inter-Dipole Distance Between Unilateral Median Versus Ulnar Nerve Stimulation of Both Hands in MEG

Abstract: Contralateral somatosensory evoked fields (SEF) by whole head MEG after unilateral median and ulnar nerve stimulation of both hands were studied in 10 healthy right-handed subjects. Major parameters describing cortical activity were examined to discriminate median and ulnar nerve evoked responses. Somatic sensitivity showed high similarity in the 4 study conditions for both hand and nerve. The brain SEFs consisted of 7-8 major peak stages with consistent responses in all subjects at M20, M30, M70 and M90. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
2
2
0
Order By: Relevance
“…Using the constructed wearable OPM-MEG, we have shown that the SEFs under median and ulnar nerve stimulations can be reliably detected by OPMs with high quality (maximum amplitude reaches 1 pT). Both the sensor-level and source-level analyses have demonstrated substantial differences in cortical responses to different stimulations of peripheral nerves, which is consistent with the findings of previous studies ( Theuvenet et al., 2006 ; Huttunen et al., 2006 ). In particular, FESSE provides more reasonable source imaging results than competing methods without adjusting the imaging threshold ( Figure 8 ).…”
Section: Discussionsupporting
confidence: 90%
“…Using the constructed wearable OPM-MEG, we have shown that the SEFs under median and ulnar nerve stimulations can be reliably detected by OPMs with high quality (maximum amplitude reaches 1 pT). Both the sensor-level and source-level analyses have demonstrated substantial differences in cortical responses to different stimulations of peripheral nerves, which is consistent with the findings of previous studies ( Theuvenet et al., 2006 ; Huttunen et al., 2006 ). In particular, FESSE provides more reasonable source imaging results than competing methods without adjusting the imaging threshold ( Figure 8 ).…”
Section: Discussionsupporting
confidence: 90%
“…Polarity reversals of the three-dimensional brain maps mainly reflect change in dipole orientation and are an indication of spatial somatosensory processing. The first and second polarity reversals, consistently seen in the three-dimensional maps in subjects and described earlier, 63 differed in the two groups. The significance of the finding is that in the patient group both reversals were less consistently observed and moreover at different latencies is yet unknown.…”
Section: Modulated Cortical Processing In Neuropathic Painsupporting
confidence: 69%
“…3D cortical mapping revealed dipolar fields at the major peak latencies with an early and late polarity reversal for both nerves, the significance for brain processing and accurate somatotopic organization is unknown but was observed earlier (Theuvenet et al 2006). The spatial dipole Fig.…”
Section: Discussionmentioning
confidence: 86%